Clastic sediments from dolines and caves found during the construction of the motorway near Divača, on the classical Karst - Mihevc, Andrej (Acta carsologica, 1996)
Dolines differ in form and size and also by the sediments in them. In numerous dolines allochtonous non-carbonate pebbles, sands and loam sediments were found. During the construction of the motorway across the Karst the works uncovered a vast number of dolines, and crossed several caves filled up by mechanical sediments. Sediment analyses showed that some depressions were actually fossil caves filled up by fluvial allochtonous sediments and later opened to the surface due to its lowering and so changed into superficial depressions
Keywords: Divača; geomorfologija; geomorphology; karst; Kras; kraške jame; List of caves in Slovenia; sedimentne kamnine; speleogeneza; vrtače